Growing Teratoma Syndrome Secondary to Ovarian Giant Immature Teratoma in an Adolescent Girl: A Case Report and Literature Review. Issue 7 (February 2016) - Li, Song; Liu, Zhenzhen; Dong, Chengyong; Long, Fei; Liu, Qinlong; Sun, Deguang; Gao, Zhenming; Wang, Liming
Abstract : Abstract: Growing teratoma syndrome (GTS) is a rare clinical entity first described by Logothetis et al in 1982. Although it is unusual for GTS to be located in the ovary, this report is of a case of an adolescent girl who underwent a complete surgical resection of the mass. Histopathology confirmed only an immature teratoma had originated from the ovary and so she received adjuvant chemotherapy with blemycin, etopside, and cisplatin over 4 cycles. Results from an abdominal enhanced CT (computed tomography) 9 years later revealed a giant mass had compressed adjacent tissues and organs. Laparotomy was performed and a postoperative histopathology showed the presence of a mature teratoma, and so the diagnosis of ovarian GTS was made. One hundred one cases of ovarian GTS from English literature published between 1977 and 2015 were collected and respectively analyzed in large samples for the first time. The median age of diagnosis with primary immature teratoma was 22 years (range 4–48 years, n = 56). GTS originating from the right ovary accounted for 57% (27/47, n = 47) whereas the left contained 43% (20/47, n = 47). Median primary tumor size was 18.7 cm (range 6–45 cm, n = 28) and median subsequent tumor size was 8.6 cm (range 1–25 cm, n = 25). From the primary treatment to the diagnosis of ovarian GTS, median tumor growth speed was 0.94 cm/month (range 0.3–4.3 cm/month, n = 21). Median time interval was 26.6 months (range 1–264 months, n = 41). According to these findings, 5 patients did have a pregnancy during the time interval between primary disease and GTS, making our patient the first case of having a pregnancy following the diagnosis of ovarian GTS. Because of its high recurrence and insensitiveness to chemotherapy, complete surgical resection is the preferred treatment and fertility-sparing surgery should be considered for women of child-bearing age. Anyhow GTS of the ovary has an excellent prognosis. Patients with GTS had no evidence of recurrence or were found to be disease free during a 40.3-month (range 1–216 months, n = 48) median follow-up. Moreover, regular follow-ups with imaging and serum tumor markers are important and must not be neglected.